Identification and genotyping of Mycobacterium tuberculosis complex infections at the human/domestic animals/wildlife interface in Nigeria and South Africa - Godfroid, Jacques (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.